2022
DOI: 10.1590/1519-6984.237809
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status and their enhancements strategies for water stress tolerance in chickpea

Abstract: Water stress executes severe influences on the plant growth and development through modifying physio-chemical properties. Therefore, a field experiment was designed to evaluate the antioxidant status and their enhancements strategies for water stress tolerance in chickpea on loam and clay loam soils under agro-ecological conditions of Arid Zone Research Institute, Bahawalpur (29.3871 °N, 71.653 °E) and Cholistan farm near Derawer (28.19°N, 71.80°E) of Southern Punjab, Pakistan during winter 2014-15. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Although, in our study was verified that higher contents of proline than a critical point might lead to negative effect on the plants. In concordance with our study, different authors showed that proline regulation application was able to decrease the negative effects of environmental stress on Trifolium repens L. 30 , tobacco 32 , Glycyrrhiza uralensis 27 , and chickpea 28 mostly via decreasing the content of H 2 O 2 and malondialdehyde and also increasing the activity of enzymatic antioxidants. Also, Zali and Ehsanzadeh 33 and 34 Showed that proline was capable of increasing the growth of fennel And Phaseolus vulgaris under water deficit conditions and nutrient deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Although, in our study was verified that higher contents of proline than a critical point might lead to negative effect on the plants. In concordance with our study, different authors showed that proline regulation application was able to decrease the negative effects of environmental stress on Trifolium repens L. 30 , tobacco 32 , Glycyrrhiza uralensis 27 , and chickpea 28 mostly via decreasing the content of H 2 O 2 and malondialdehyde and also increasing the activity of enzymatic antioxidants. Also, Zali and Ehsanzadeh 33 and 34 Showed that proline was capable of increasing the growth of fennel And Phaseolus vulgaris under water deficit conditions and nutrient deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…The plants under water stress showed an increase in antioxidant enzyme activity, as also reported by Sachdev et al [43]. It has been reported that the upregulation of antioxidants is helpful in drought tolerance in different plants, such as maize [44] and chickpea [45]. In this study, under water stress, the foliar application of ZnNPs and ZnSO 4 helped to maintain SOD, POD, and CAT activities.…”
Section: Discussionsupporting
confidence: 82%
“…Owing to unpredicted changes in climate, pulses become more sensitive to oxidative damage by the overproduction of ROS such as H 2 O 2 , hydroxyl, and superoxide radicals. Specialized enzymatic antioxidants, i.e., POD, SOD, APX and CAT, are activated and act as the first line of defense for detoxification of the effects of ROS [ 51 ]. In the present study, increased activity of SOD, POD, CAT, and APX was investigated in all genotypes under drought-stressed conditions over the normal condition.…”
Section: Discussionmentioning
confidence: 99%
“…An integrated approach involving physio-biochemical traits and multi-environmental yield trials was performed for screening and selecting drought-tolerant chickpea genotypes and allowed us to conclude that higher RWC, CMS, glycine betaine, and proline content conferred a more significant capability for drought stress tolerance in chickpea [ 16 ]. In another investigation, the reduction in growth and yield of the tolerant cultivar was less compared to the susceptible cultivar DUSHT, probably due to the accumulation of higher antioxidant enzyme activities, suggesting the protective role of enhanced antioxidant enzyme activities of plants under water-stressed conditions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%